Mythopoetical analysis of the kazakh story of the second half of the XX century (Eurasian Journal of Philology Science and Education, 2023)
In modern Kazakh prose, works written in Russian are of great importance. The Russian-language Kazakh prose of the 60s of the XX century turned into a historical fact not only of Kazakh literature, but also of Kazakh culture. Representatives of the Kazakh Russian-language literature make attempts to comprehend the new reality by artistic means, recreate pictures of a distant history. Kazakh literature has managed to preserve its national identity, because it has always relied on folk traditions, on centuries-old cultural heritage. The article deals with the main mythological motifs and images found in the stories of S. Sanbaev and A. Alimzhanov. The features of their author's mythologism, the refraction of the myth in the context of modernity are studied. The necessity of using the mythopoetic method for understanding the philosophical subtext of a work of art and the author's intention as a whole is substantiated. The author analyzes the symbolic meaning of the names of the heroes of the works, reveals the archetypal image of the old man, the mythology of blindness and insight, etiological and totemic myths are intertwined with the motives of Tengrism. The article substantiates the close relationship between man and nature in the spirit of syncretic mythological consciousness. In conclusion, the author dwells on the advantages of this method in the interpretation of the text.Key words: myth, mythologeme, archetype, image, mythopoetics.